Consumers' attitude footprint on sustainable development in developed and developing countries: a case study in the electronic industry - Ghorbanloo, Sanaz; Shokouhyar, Sajjad (Operations management research, 2023)
Mobile phones, often known as cell phones, have grown in popularity to the point that they are now almost necessary in today's lifestyle. However, its manufacture, usage, and disposal can impose enormous economic, social, and environmental costs. In recent years, economic, social and environmental concerns have become global public attention. This is particularly true for electronic products like cellphones, which are the subject of this paper. Therefore, consumer electronics should create social and environmental values while achieving positive economic results. Due to consumers’ different behavior based on their local situation, this study looks at people’s perspectives on cellphone sustainability in developing and developed countries. According to the triple bottom line principle, it is crucial for countries to have a responsible attitude toward society and the environment to achieve sustainable development, as well as a concentration on economic profit. Therefore, a mixed method of quantitative and qualitative approaches (based on Twitter data and thematic analysis of literature) has been adopted. In this research, content analysis, descriptive analysis, and sentiment analysis are used to analyze both quantitative and qualitative content for research methodology which is provided with a lexicon-based approach based on Twitter data to identify the most frequent dimensions of “sustainability” that customers perceive. We collected over a hundred-thousand tweets using the Twitter Application Programming Interface (API) over Twenty months. In terms of the three dimensions of "sustainable development," the data show that the "economic" feature is the most important in developing countries, while the "environmental" dimension is the least important. Further analysis shows that the effects of these aspects differ between developed and developing countries. On the other side, due to higher welfare in the developed world, the priority of these aspects included, the "environmental", "social" and lastly "economic" dimensions.